La gouvernance urbaine en question: le cas des lieux de nature cultivée - Paula Nahmias (Éditions en environnement VertigO, 2012)
Metropolitan growth is a powerful geographical-economic phenomenon that transforms both conditions and forms of governance at different scales, especially local scales: inter-urban competition for the attraction of people and activities, importance of public-private action, rise of the claims from organized civil society. Places of cultivated nature in the city are crossed by these mutations of governance. The article aims to show that the multifunctional character of these places of nature (ecological health, food resource, hub of social interactions and individual attachment) produces some “spaces issues” for those involved in urban planning. Indeed, objectives of urban institutions come into tension with the expression of the demands of inhabitants, because there are different views about the lived and practiced spaces. From the example of the city of Rennes, in western France, we can question the ability of urban institutions to provide local democracy from residents participation, and to effectively integrate all forms of productive activities in a shared metropolitan project.